2021
DOI: 10.3390/ani11030837
|View full text |Cite
|
Sign up to set email alerts
|

Finding Purpose in the Conservation of Biodiversity by the Commingling of Science and Ethics

Abstract: Averting the biodiversity crisis requires closing a gap between how humans tend to behave, individually and collectively, and how we ought to behave—“ought to” in the sense of behaviors required to avert the biodiversity crisis. Closing that gap requires synthesizing insight from ethics with insights from social and behavioral sciences. This article contributes to that synthesis, which presents in several provocative hypotheses: (i) Lessening the biodiversity crisis requires promoting pro-conservation behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 116 publications
0
8
0
Order By: Relevance
“…This finding highlights the degree to which moral beliefs drive both sides of the trophy hunting debate. Moreover, it emphasizes the need for more interdisciplinary work on conservation ethics, which should involve both scientists and humanities scholars (Vucetich, Macdonald, et al, 2021). We also found that trophy hunting's consequences for local communities were the most salient predictor of both opponents' and proponents' views.…”
Section: Discussionmentioning
confidence: 99%
“…This finding highlights the degree to which moral beliefs drive both sides of the trophy hunting debate. Moreover, it emphasizes the need for more interdisciplinary work on conservation ethics, which should involve both scientists and humanities scholars (Vucetich, Macdonald, et al, 2021). We also found that trophy hunting's consequences for local communities were the most salient predictor of both opponents' and proponents' views.…”
Section: Discussionmentioning
confidence: 99%
“…I agree the necessity, potency and ethical imperative of the integration, although as a conservation biologist and practitioner I have always included animal welfare as an important arrow in the quiver of conservation considerations [ 132 , 133 , 134 , 135 , 136 ] (Macdonald & Boitani 1979, Macdonald and Dawkins 1981, Macdonald 2001, Macdonald et al 2006a, Macdonald and Willis 2013). In a way compatible with non-anthropocentrism [ 22 , 137 ] (Vucetich et al 2018a. 2021), the experiences of animals themselves are central to Beausoleil et al’s [ 21 ] (2018) conception of welfare.…”
Section: Synergies Between Animal Welfare and Biodiversity Conservationmentioning
confidence: 99%
“…Towards the other end of a continuum of positions, a consequentialist view, while striving to minimise suffering might offset any residual welfare disbenefit against potential conservation benefits. In charting a route to an ethically sound framework for conservation, that incorporates animal welfare and is non-anthropocentric, Vucetich et al [ 22 ] (2021) review these two ethical frameworks, Kantian deontology and the consequentialism or utilitarianism generally associated with Jeremy Bentham and John Stuart Mill. They also introduce a third, yet more venerable, framework, virtue ethics, which emphasises virtues and the Aristotelian quest for well-being termed eudemonia, ‘a word that while not readily translated into English, refers to a kind of human flourishing, a rich sense of happiness that transcends hedonism’.…”
Section: Balancing Welfare With Other Prioritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of human-wildlife interactions (HWIs), the effects of which include collisions with vehicles, damage to property and agricultural production, zoonotic diseases, and the use of animals as a resource, is becoming more challenging (Broad et al, 2014;Aguirre, 2017;Pooley et al, 2017;IUCN, 2020). Behind this trend are the rapid and profound changes in the physical environment and societal values associated with the Anthropocene and modernization, including factors such as climate change, expanding infrastructure, urbanization, economic globalization, the digital revolution, and the expanding scope of ethical considerations (Vucetich et al, 2021a). One view, that we share, is that in an increasingly complex and interconnected human-dominated world, turning HWI into large-scale coexistence requires thorough planning (Marchini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%